Exploring the new media influences on social engagement among youths in the Institute of Higher Education (IPT) - Shekh Alsagoff, Syed Agil; Abdullah, Amini Amir; Abdu, Arifin (Penerbitan Korporat UMK, 2024)
The study explores the influence of new media on social engagement among youths in Institutes of Higher Education (IPT) in Malaysia. Utilizing Media Dependency Theory and a qualitative approach through focus Instagram, and others impacts their social behaviors and engagement. The findings reveal that new media plays a significant role in shaping youths' social interactions, both positively and negatively, by facilitating communication and engagement while also contributing to issues such as addiction and cyberbullying. The study highlights four main themes community development, digitalization technology development, positive youth development, and society development each revealing how new media influences youth in distinct ways. It was observed that while new media fosters a sense of community and provides avenues for positive development, it also presents risks such as decreased self-esteem and increased exposure to harmful content. The research concludes that there is a critical need for better management of new media usage among youths, advocating for educational initiatives that promote safer online practices and more effective use of digital platforms to enhance positive social engagement. This study offers valuable insights into the complex dynamics between new media usage and youth behavior, providing a foundation for future research and policy development aimed at mitigating the negative impacts while leveraging the positive potential of new media.